Titin isoform size is not correlated with thin filament length in rat skeletal muscle - Greaser, Marion L.; Pleitner, Jonathan M. (Frontiers in Physiology, 2014)
The mechanisms controlling thin filament length in muscle remain controversial. It was recently reported that thin filament length was related to titin size, and that the latter might be involved in thin filament length determination. Titin plays several crucial roles in the sarcomere, but its function as it pertains to the thin filament has not been explored. We tested this relationship using several muscles from wild type rats and from a mutant rat model which results in increased titin size. Myofibrils were isolated from skeletal muscles (extensor digitorum longus, external oblique, gastrocnemius, longissimus dorsi, psoas major, and tibialis anterior) using both adult wild type (WT) and homozygous mutant (HM) rats. Phalloidin and antibodies against tropomodulin-4 and nebulin’s N-terminus were used to determine thin filament length. The WT rats studied express skeletal muscle titin sizes ranging from 3.2 to 3.7 MDa, while the HM rats express a giant titin isoform sized at 3.7 MDa. No differences in phalloidin-based thin filament length, nebulin N terminus distances from the Z line, or tropomodulin distances from the Z line were observed across genotypes. The data indicates that, although titin performs many sarcomeric functions, its correlation with thin filament length and structure could not be demonstrated in the rat. Current models of thin filament assembly are inadequate to explain the phalloidin, nebulin N terminus, and tropomodulin staining patterns in the myofibril.